"The new normal has become a nonstop crisis": a qualitative study of burnout among Philadelphia's harm reduction and substance use disorder treatment workers during the COVID-19 pandemic - Ijeoma C. Unachukwu; Matthew P. Abrams; Abby Dolan; Kehinde Oyekemi; Zachary F. Meisel; Eugenia C. South; Shoshana V. Aronowitz (BMC, 2023)
Abstract Background The COVID-19 pandemic worsened the ongoing overdose crisis in the United States (US) and caused significant mental health strain and burnout among health care workers (HCW). Harm reduction, overdose prevention, and substance use disorder (SUD) workers may be especially impacted due to underfunding, resources shortages, and chaotic working environments. Existing research on HCW burnout primarily focuses on licensed HCWs in traditional environments and fails to account for the unique experiences of harm reduction workers, community organizers, and SUD treatment clinicians. Methods We conducted a qualitative secondary analysis descriptive study of 30 Philadelphia-based harm reduction workers, community organizers, and SUD treatment clinicians about their experiences working in their roles during the COVID-19 pandemic in July-August 2020. Our analysis was guided by Shanafelt and Noseworthy's model of key drivers of burnout and engagement. We aimed to assess the applicability of this model to the experiences of SUD and harm reduction workers in non-traditional settings. Results We deductively coded our data in alignment with Shanafelt and Noseworthy's key drivers of burnout and engagement: (1) workload and job demands, (2) meaning in work, (3) control and flexibility, (4) work-life integration, (5) organizational culture and values, (6) efficiency and resources and (7) social support and community at work. While Shanafelt and Noseworthy's model broadly encompassed the experiences of our participants, it did not fully account for their concerns about safety at work, lack of control over the work environment, and experiences of task-shifting. Conclusions Burnout among healthcare providers is receiving increasing attention nationally. Much of this coverage and the existing research have focused on workers in traditional healthcare spaces and often do not consider the experiences of community-based SUD treatment, overdose prevention, and harm reduction providers. Our findings indicate a gap in existing frameworks for burnout and a need for models that encompass the full range of the harm reduction, overdose prevention, and SUD treatment workforce. As the US overdose crisis continues, it is vital that we address and mitigate experiences of burnout among harm reduction workers, community organizers, and SUD treatment clinicians to protect their wellbeing and to ensure the sustainability of their invaluable work.